2006
DOI: 10.1111/j.1471-4159.2006.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of N‐acetylaspartate and N‐acetylaspartylglutamate biosynthesis by protein kinase activators

Abstract: The neuronal dipeptide N-acetylaspartylglutamate (NAAG) is thought to be synthesized enzymatically from N-acetylaspartate (NAA) and glutamate. We used radiolabeled precursors to examine NAA and NAAG biosynthesis in SH-SY5Y human neuroblastoma cells stimulated with activators of protein kinase A (dbcAMP; N6,2¢-O-dibutyryl cAMP) and protein kinase C (PMA; phorbol-12-myristate-13-acetate). Differentiation over the course of several days with dbcAMP resulted in increased endogenous NAA levels and NAAG synthesis fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…NAAG synthesis from radiolabeled amino acids is insensitive to inhibition of protein synthesis as demonstrated both in spinal sensory ganglia in vivo (11) or in isolated spinal cords (12). Furthermore, labeling studies in vivo (24), in spinal cords (12) and in SH-SY5Y human neuroblastoma cells (25) all indicate that NAA is a better precursor for NAAG than free aspartate. Finally, almost four decades ago Reichelt and Kvamme (19) demonstrated the existence of NAAG synthesis in homogenates of mouse brain and showed it to be absolutely dependent on the presence of ATP.…”
Section: Agreement With Previous Results Suggesting That Naag Ismentioning
confidence: 88%
“…NAAG synthesis from radiolabeled amino acids is insensitive to inhibition of protein synthesis as demonstrated both in spinal sensory ganglia in vivo (11) or in isolated spinal cords (12). Furthermore, labeling studies in vivo (24), in spinal cords (12) and in SH-SY5Y human neuroblastoma cells (25) all indicate that NAA is a better precursor for NAAG than free aspartate. Finally, almost four decades ago Reichelt and Kvamme (19) demonstrated the existence of NAAG synthesis in homogenates of mouse brain and showed it to be absolutely dependent on the presence of ATP.…”
Section: Agreement With Previous Results Suggesting That Naag Ismentioning
confidence: 88%
“…It is synthesized enzymatically from NAA and glutamate (Arun et al, 2006;Boltshauser et al, 2004;Cangro et al, 1987;Gehl et al, 2004) and is localized in specific types of neurons throughout the CNS (Anderson et al, 1987;Moffett et al, 1993;Moffett and Namboodiri, 1995;Tieman et al, 1991;Tieman and Tieman, 1996). NAAG is released from synapses in a calcium dependent manner (Williamson et al, 1991), and acts through presynaptic metabotropic glutamate receptors to modulate the release of classical neurotransmitters (Xi et al, 2002;Zhao et al, 2001).…”
Section: Naa and Naag Biosynthesismentioning
confidence: 99%
“…The presence of a "NAAG synthetase" enzyme has been postulated based on indirect means in several studies (Arun et al, 2006;Cangro et al, 1987;Gehl et al, 2004;Urazaev et al, 2001;Williamson and Neale, 1988). Most recent studies which have successfully demonstrated NAAG biosynthesis were done in neural explants, including excised rat dorsal root ganglia (Cangro et al, 1987), excised frog retinas (Williamson and Neale, 1988), crayfish nerve cord (Urazaev et al, 2001) and hemisected rat spinal cord (Gehl et al, 2004).…”
Section: Evidence For a Naag Synthetase Enzymementioning
confidence: 99%
See 2 more Smart Citations